Efektivitas Citizen Relation Management (CRM) dalam Penyelenggaraan Penanganan Pengaduan Masyarakat di Wilayah Kota Administrasi Jakarta Timur Tahun 2021 - Nadea Rahmadani Azzahra; Ainun Nazriah (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
The Citizen Relations Management (CRM) application program is an innovation from the DKI Jakarta government which aims to make it easier for the SKPD to accommodate, coordinate, and handle all complaints or reports regarding problems experienced by the community. This CRM application can only be used by DKI Jakarta government officials. The problems most often reported by the community through the CRM application include 1) garbage; 2) disturbance of public order and comfort; 3) illegal parking; 4) violation of regional regulations; 5) traffic jams. The purpose of this study was to determine the effectiveness of CRM applications in handling public complaints, and to find out the inhibiting and supporting factors of CRM applications in handling public complaints. The theory used in this study is the theory of effectiveness measures put forward by Duncan in Richard M. Steers with 3 (three) indicators namely goal attainment, integrity, and adaptation. This study uses qualitative methods, informant selection techniques are determined purposively, and data collection techniques used are observation, interviews, documentation related to research, then the data obtained will be analyzed by means of data reduction, data presentation, and drawing conclusions. The results of the study show that the application of the CRM application program in handling public complaints can be said to be effective and in accordance with the objectives of using the CRM application, namely, to make it easy for SKPD to handle complaint reports and make it easy for people who want to report the problems they are experiencing based on the phenomenon of achieving goals, integrity, and adaptation. Then the CRM application consists of 14 official complaint channels that can be used by the public. The implementation of the CRM application program has several supporting factors, namely human resources who understand technology and use CRM applications, then there are supportive leadership policies, and the CRM application function is said to be a supporter of SKPD in handling public complaints. In addition, there are factors that become obstacles in the running of this CRM application, namely, community reports that have no explanation, people who are just playing around in making reports, and difficulty signaling due to bad weather.